AI or i? exploring student attitudes toward AI-assisted article analysis - Saad, Sharina; Abdul Rahman, Azlan; Nur Morat, Berlian (Universiti Teknologi MARA, Kedah, 2025)
Article analysis is a vital academic skill that requires critical thinking and analytical abilities. This study explores how artificial intelligence (AI) influences students’ approaches to article analysis, focusing on their attitudes, reliance on AI tools, and the impact on critical thinking and academic integrity. Using a mixed-methods approach, data were collected through surveys and interviews across various academic disciplines. Results indicate widespread use of AI tools, primarily for summarizing and brainstorming, reflecting their growing integration into student workflows. Despite these benefits, students expressed concerns about potential overdependence on AI, which may hinder their critical thinking development. Ethical considerations regarding academic honesty were also prominent. The findings highlight the need for clear educational guidelines to ensure AI supports learning without compromising essential academic skills. This study contributes to understanding the balanced integration of AI in higher education.